SATISFACTION ANALYSIS OF OUTPATIENT SERVICE QUALITY USING SERVQUAL - Widdy Kurniawan Santoso; Marchaban Marchaban; Riswaka Sudjaswadi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Medical service companies are getting more competitive so companies have to always improve the service quality. The Pharmacy Unit of Yakkum Emanuel Hospital which is a supporting medical unit is demanded to give an optimal service to their patients. The recapitulation of the complaint box in February 2011 showed that 50% of patients (10 patients) complain on waiting time; 30% of patients (6 patients) complain on the hot air in the waiting room; and 20% of patients (4 patients) complain about when the patients will get their medicine. Regarding those issues, this research aimed to analize the level of patient satisfaction on the service quality at pharmacy unit of Yakkum Emanuel Hospital. This research was conducted with descriptive method. The subjects of this research were outpatient in Yakkum Emanuel Hospital that met the inclusion criteria. The number of the sample was 480 patients that taken with purposive method of sampling. The data were obtained using quetionaire about the quality of service based on SERVQUAL model (referring to tangibles, reliability, responsiveness, assurance, and empathy dimensions) and the data were mapped in cartesian diagram. The result shows that there were negative gap values between the patients’ expectation and perception. The highest gap value was on the assurance dimension followed by responsiveness, reliability, empathy, and tangibles dimensions. In general, patients felt dissatisfied with the performance of the management of the Pharmacy Unit of Yakkum Emanuel Hospital Purwareja-Klampok. Based on the Cartesian Diagram mapping, the management of the Pharmacy Unit of Yakkum Emanuel Hospital should pay more attention to the Assurance and Responsiveness dimensions.Keywords: service quality, satisfaction, SERVQUAL.